THE INFLUENCE OF TEACHER' GENDER ATTITUDES IN FORMING OF VALEOLOGICAL CULTURE OF JUNIOR STUDENTS - Ірина Шульга (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article explains actuality of gender socialization of junior pupils in primary school. The organization of educational process in the gender paradigm is described. In particular, content of first teachers' gender views as to forming of the valeological culture of junior pupils through the prism of approaches (stereotyped and personal-oriented) and interaction in system "teacher-student" is given. The results of the empirical study of primary school teachers' gender attitudes and conceptions as to educational process for boys and girls are presented. Considerable gender stereotyping of consciousness of primary school teachers is shown. It confirms the prevalence of traditional sex-role requirements for education and behavior of boys and girls and its impact on forming of junior students' valeological competence.